Remote sensing restores predictability of ectotherm body temperature in the world’s forests - Algar, Adam C.; Morley, Kate; Boyd, Doreen S. (Wiley, 2018)
AIM: Rising global temperatures are predicted to increase ectotherms’ body temperatures, benefitting some species but threatening others. Biophysical models predict a key role for shade in buffering these effects, but the difficulty of measuring shade across broad spatial extents limits predictions of ectotherms’ thermal futures at the global scale. Here, we extend biophysical models of ectotherm body temperature to include effects of forest canopy shade, via leaf area index, and test whether considering remotely-sensed canopy density improves predictions of body temperature variation in heavily shaded habitats. LOCATION: Worldwide. TIME PERIOD: 1990–2010. MAJOR TAXA STUDIED: Lizards. METHODS: We test predictions from biophysical ecological theory for how body temperature should vary with microclimate for 269 lizard populations across open, semi-open, and closed habitats worldwide. We extend existing biophysical models to incorporate canopy shade effects via leaf area index, test whether body temperature varies with canopy density as predicted by theory, and evaluate the extent to which incorporating canopy density improves model performance in heavily-shaded areas. RESULTS: We find that body temperatures in open habitats, like deserts, vary with air temperature and incident solar radiation as predicted by biophysical equations, but these relationships break down in forests, where body temperatures become unpredictable. Incorporating leaf area index into our models revealed lower body temperatures in more heavily shaded environments, restoring the predictability of body temperature in forests. CONCLUSIONS: Although biophysical ecological theory can predict ectotherm body temperature in open habitats, like deserts, these relationships decay in closed forests. Models incorporating remotely sensed data on canopy density improved predictability of body temperatures in these habitats, providing an avenue to incorporate canopy shade effects into predictions of animals’ vulnerability to climate change. These results highlight the thermal threat of changes in canopy structure and loss of forest cover for the world’s ectotherms.